2013
DOI: 10.5125/jkaoms.2013.39.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of multiple myeloma in the head and neck: a report of two cases

Abstract: Multiple myeloma (MM) is a disease reported to account for 1% of all cancers and 10% of hematological malignant diseases. Unlike other malignant diseases that are transferred to the osseous tissues, MM does not show new bone formation, is associated with characteristic osteolytic lesions, and shows monoclonal protein (M-protein) on the immunohematological test, which is an important index in its diagnosis. Solitary lesions of MM are rare in the head and neck area, and, in most cases, MM of the head and neck ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…MM is a disease related to a hematological disorder that appears at various stages of β-cells, and it accounts for 1% of all cancers, as well as 10% of hematological malignancies [32,33]. Based on recent studies, miRs have been identified as tumor-suppressor genes and play important roles in tumor pathogenesis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…MM is a disease related to a hematological disorder that appears at various stages of β-cells, and it accounts for 1% of all cancers, as well as 10% of hematological malignancies [32,33]. Based on recent studies, miRs have been identified as tumor-suppressor genes and play important roles in tumor pathogenesis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…4,[11][12][13] Usually, MM appears via imaging as radiolucency in the jaw and the patient may also complain of pain, swelling and mobile teeth. 3,13 In the present case, the patient was in complete remission when she presented with lip numbness. Initial assessment and routine imaging failed to identify the cause of this sudden neuropathy; however, an MRI scan revealed an altered soft tissue signal with a mass in relation to the inferior alveolar and mental nerves.…”
Section: Discussionmentioning
confidence: 50%